Peran Moderasi Strategi Bisnis Di Antara Thin Capitalization Rule Dan Penghindaran Pajak - Ranindya Hendrastuti; Eko Ganis Sukoharsono; Syaiful Iqbal (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This  study  aims  to  analyze the  effect  of  thin capitalization rule  on  tax avoidance  moderated  by  business strategy. Methodology/approach: The research method used is a quantitative approach with secondary data. Samples were taken  using  purposive  sampling and confirmatory factor analysis result ranking to  obtain  30  multinational companies   registered   on   the   IDX during  the  2014-2019  period excluded multinational companies which are not PMK-169 subject.  So, the total observations data is 180. The research analysis techniques using hierarchical regression analysis. Findings: The results showed that business strategy can moderate between thin capitalization rule and tax avoidance. The defender business strategy weakens the negative influence of the Thin Capitalization Rule on tax avoidance, whereas the prospector business strategy strengthens the negative influence of the Thin Capitalization Rule on tax avoidance. Practical implications: The government could consider easing the Thin Capitalization Rule for companies operating in business sectors dominated by prospectors and tightening the rules for companies operating in business sectors dominated by defenders. Originality/value: There    are    still   no    research references    regarding    thin capitalization rule    on    tax avoidance   moderated   by   business strategy.   This research develops previous research by adding business strategy with confirmatory factor analysis in the moderation model.